Habitat choice versus habitat transformation in a nest-building fish: which matters most?. (4th April 2022) - Dhamelincourt, Marius; Rives, Jacques; Lange, Frédéric; Elosegi, Arturo; Tentelier, Cédric
Abstract: Animals of many species lay their eggs in nests built to provide their offspring a suitable microhabitat during a critical phase of development. Nest characteristics result from two processes: habitat choice and modification that may impact differently nest suitability for eggs. This field-based study aimed to estimate their independent effects and their interaction effects on the capacity of sea lamprey nests to retain eggs. Physical variables linked to both habitat choice and habitat modification affected nest suitability, but higher effect sizes indicated the prevalence of habitat modification. The most retentive nests were built in habitats with slower current (habitat choice) and had steeper slope between the deepest part of the nest (pit) and the downstream mound (habitat modification); the positive effect of the steep slope increasing with flow velocity in the nest. Our results show that habitat choice and habitat modification must be taken into account in evolutionary or conservation studies that analyze nest-building animals. Abstract : Many animals dig nests to provide good conditions for their progeny. Nevertheless, the distinction between the importance of the choice of habitat compared with the characteristics of the modifications made during nest building is little considered. Using the sea lamprey as a study case, it appears that both choice and modification should be considered but that habitat modification had a greater impact on keeping eggs in the nest.